They were just people : stories of rescue in Poland during the Holocaust - Tammeus, Bill; Cukierkorn, Jacques (2009)
"Tammeus and Cukierkorn interview Jewish survivors and their non-Jewish rescuers, capturing for future generations stories of how, through courage and ingenuity, a few Jews in Poland escaped the Holocaust, and revealing how individuals can preserve civility and compassion even in the face of overwhelming evil"–Provided by publisher